Does acute promyelocytic leukemia in Indian patients have biology different from the West? - Dutta Pankhi; Sazawal Sudha; Kumar Rajat; Saxena Renu (Wolters Kluwer Medknow Publications, 2008)
Acute promyelocytic leukemia (APML) is a well-characterized malignancy with typical clinico-hematological and molecular features. However, Indian data on this malignancy are limited. This study was conducted to determine the clinico-hematological profile of APML in India. Thirty-five patients with APML presenting to Hematology Department, AIIMS, New Delhi, between July 2003 and June 2005 were evaluated for presenting clinical features, hemogram, peripheral smear, bone marrow morphology and cytochemistry. Reverse transcriptase PCR (RT-PCR) for PML-RARα was done in all cases. Male-to-female ratio was 0.9:1 (males - 17 and females - 18) with median age 25 years (range 11-57 years). Presenting features included anemia, bleeding, fever, gum hypertrophy and scrotal ulceration. All cases showed hypergranular abnormal promyelocytes. Median hemoglobin was 6.3 g/dL (range - 3.0-9.0 g/dL), total leukocyte count (TLC) was 33.88 x 10 9 /L (range - 1-170 x 10 9 /L). Platelet count was 28 x 10 9 /L (range - 4-170 x 10 9 /L). All cases were positive for myeloperoxidase and sudan black (SB), whereas 60% cases also showed non specific esterase (NSE) positivity with 40% cases being fluoride sensitive. RT-PCR showed PML-RARα in 33/35 cases with the bcr3 isoform being present in 24/33 positive cases (72.7%). The two cases negative for PML-RARα showed typical morphology and responded to ATRA. On statistical analysis, no correlation was found between bcr isoform and TLC, platelet count, age sex and early death. Unusual features included gum hypertrophy and scrotal ulceration at presentation and high median presenting TLC (33.8 x 10 9 /L). There was, however, no microgranular variant. Another interesting feature was a high incidence of NSE positivity (60%), which was fluoride sensitive in 40%. Moreover, the bcr3 isoform was significantly overexpressed (72.7%) in comparison to other studies. APML in India has certain unusual features, which may reflect a different biology.